Why are the prevalence and diversity of helminths in the endemic Pyrenean brook newt Calotriton asper (Amphibia, Salamandridae) so low?. Issue 2 (25th October 2013) - Comas, M.; Ribas, A.
Abstract: A cornerstone in parasitology is why some species or populations are more parasitized than others. Here we examine the influence of host characteristics and habitat on parasite prevalence. We studied the helminths parasitizing the Pyrenean brook newt Calotriton asper ( n = 167), paying special attention to the relationship between parasites and ecological factors such as habitat, sex, ontogeny, body size and age of the host. We detected two species of parasites, Megalobatrachonema terdentatum (Nematoda: Kathlaniidae) and Brachycoelium salamandrae (Trematoda: Brachycoeliidae), with a prevalence of 5.99% and 1.2%, respectively. Marginally significant differences were found in the prevalence between sexes, with females being more parasitized than males. The present results show significant differences in the body length of paedomorphic and metamorphic individuals, the former being smaller. Nevertheless, no significant correlations between parasite prevalence and either newt body length, ontogenetic stage or age were found. In comparison with other Salamandridae living in ponds, prevalence and diversity values were low. This may be due to a long hibernation period, the species' lotic habitat and its reophilous lifestyle, which probably do not allow for a high parasite load.